Atrial fibrillation after Coronary Artery Bypass Surgery with and without Cardiopulmonary Bypass (Cardiovascular Journal, 2018)
Background:Atrial fibrillation (AF) is the most common postoperative supraventricular arrhythmi. 20% to 40% of patients have AF after coronary artery bypass operation (CABG).Arrhythmia of all grades may occur due to cardiopulmonary bypass (CPB) and injuries inflicted during operativeprocedures. Thus it has been proposed that CABG surgery would be safer if CPB could be avoided.Methods:Total 60 patients who underwentCABG were selected for the study and divided in two groups. Group A: 30 patients with Off-pump CABG (OPCAB) and Group B: 30 patients with On-pump CABG. 12 lead ECG was done at morning on the day of surgery, after surgery & when any arrhythmia are noted for at least 7days. Morbidity of patients like arrhythmia and hospital mortality were recorded and compared during the first week after surgery.Results:Off-pump group (group- A) had less incidence of post-operative AF than on-pump group(group-B) (10% vs 40%). Postoperative blood requirement,total operative time, the period of mechanical ventilation,ICU stay and total postoperative hospital stayis significantly shorter in off-pump than in on-pump group of patients.Conclusion: This study clearly demonstrates that off pump CABG procedure is associated with less incidence of AF. Therefore OPCAB procedure for myocardial revascularization is clearly justified whenever feasible.Cardiovasc. j. 2018; 10(2): 171-179